Studi Pengaruh Nilai Availability Mesin Stamping Terhadap Jumlah Hasil Produksi - Purba, Adi Syahputra; Leksonowati, Nur Fitria Pujo; Pamungkas, Nurman; Yuniarsih, Nidia; Batubara, Ninda Hardina; Prasetyo, Dimas (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2024)
This study aims to analyze the effect of machine availability on production output at PT XYZ. Data collection was conducted from January to March 2024, focusing on machine downtime, total operational hours, and weekly production output. The method used involves the calculation of Mean Time Between Failure (MTBF), Mean Time To Repair (MTTR), and availability, followed by a correlation analysis between availability and production output. The results show a strong correlation between availability and output, with a correlation value of 0.852. In Week 6 and Week 11, machine downtime caused availability to drop to 98.41% and 97.96%, respectively, which directly impacted production output. Based on these findings, it is recommended that PT XYZ improve preventive maintenance and minimize downtime to maintain optimal machine availability and maximize production output